Fast and efficient intra mode decision for HEVC, based on dual-tree complex wavelet - Pakdaman, Farhad; Hashemi, Mahmoud-Reza; Ghanbari, Mohammad (Multimedia tools and applications, 2017)
The new video coding standard, High Efficiency Video Coding (HEVC) uses up to 33 angular intra modes to achieve better coding efficiency in intra coding. While larger number of modes results in a significant increase in coding efficiency than its predecessor H.264/AVC, it leads to much more complexity. To reduce this complexity, this paper proposes a novel method based on the dual-tree complex wavelet Transform (CWT). As CWT is effectively capable of representing edges in various directions, it is used to estimate the best intra angular mode in each coding block. The encoder then only analyzes a few modes around the best estimated mode. The experimental results show that searching only six modes around the estimated mode (estimated mode ± 3) plus DC and planar can predict the best mode in almost 80 % of the times. In fact the remaining unpredicted blocks have such unspecified behavior that even their random selections do not have any side effects. With all-intra configuration, searching with this method among the estimated mode ± 3 and DC and planar can improve the intra frame coding time by up to 4–10 times faster and can save the total encoding time over 32 %, while causing less than 0.4 % increase in bitrate and preserving the quality.